Tindak Lanjut Asesmen Pembelajaran Kurikulum Outcome Based Education di Pendidikan Tinggi - Idil Saptaputra; Musthofa Musthofa; Ahmad Arifi; Sitti Marwiyah (PAKAR Pendidikan, 2023)
Follow-up of learning assessment results is an action that needs to be taken in education units, including higher education. Follow-up will correct any weaknesses and learning deficiencies. This study aims to determine the implementation of the outcome based education (OBE) curriculum in higher education and the follow-up of learning assessment results in higher education. This research is a qualitative research type of literature study. So that it will review some literature derived from journal articles, books, and various regulations in connection with the focus of research, then analyzed with content analysis techniques. The results of the study show that the implementation of the OBE curriculum in higher education leads to graduate learning outcomes, carried out through the OBC stage or curriculum development by CPL, OBLT or learning implementation according to CPL, as well as OBAE or learning evaluation and assessment for CPL. Follow-up of learning assessment results is carried out based on the type of assessment. If formative assessment or assessment at the beginning and during the learning process or before the end of the semester, then the follow-up provided is problem-based learning by identifying and solving problems, complete learning by carrying out unit learning, and enrichment programs by providing further material reading. As for summative assessment or assessment at the end of the semester, the follow-up provided is a remedial program with reteaching, as well as an alternative program, namely an accelerated program with semester jumps and an independent campus by participating in internships, teaching campuses, and student exchanges.